Vous êtes sur la page 1sur 2

d(a, x) + d(x, a ) 2r diam(A) 2r

r = diam(A)+d(a, x) a A d(a , x) d(a , a)+d(a, x) diam(A) + d(a, x) = r

A

B(x, r) x

X

r

X

>

0

r

>

0

a, a

B(x, r)

A

d(a, a )

x

A

a A

diam(A) diam(A)

b, b

d(b, b ) d(b, a) + d(a, a ) + d(a , b ) ε + diam(A) + ε

A

a, a

A

a B(b, ε) a

B(b , ε)

0

ε > 0

ε

>

d(b, b ) diam(A) diam(A) diam(A)

d(A, B) = inf aA,bB d(a, b) A B c, c A B d(c, c ) diam(A) + d(A, B) + diam(B) c, c A d(c, c ) diam(A) c, c B c A c B ε > 0 d(A, B) a A b B d(a, b) d(A, B) + ε d(c, c ) d(c, a) + d(a, b) + d(b, c ) diam(A) + d(A, B) + ε + diam(B) ε d(c, c ) diam(A) + d(A, B) + diam(B) A B diam(A B) diam(A) + d(A, B) + diam(B)

d 1 ((u n ) nN , (v n ) nN ) = |v n u n | ≤ |v n | + |u n |

n

n

n

(w n ) l 1

(u n ), (v n )

d 1 ((u n ), (w n )) = |w n u n | = |w n v n + v n u n | ≤ |w n v n | + |v n u n |

n n

n n

d 1 ((u n ), (w n )) d 1 ((u n ), (v n )) + d 1 ((v n ), (w n ))

(δ k ) k

δ k,n = 0 k

= n δ k,k

= 1

k d 1 (δ k , 0) = 1 (δ k ) kN (δ k ) kN

k 1 , k 2 d 1 (δ k 1 , δ k 2 )

(δ k ) kN d 1 (δ k 1 , δ k 2 ) = 2 k 1

=

k 2

a 1 , ··· , a n a

2

i

( a i ) 2

(d 2 ((u n ) nN , 0)) 2 (d 1 ((u n ) nN , 0)) 2

(u n ) nN

l 1

k > 0 a > 0 (u k,n ) nN

d 1 ((u k,n ) nN , 0) = k 1a

0.5 < a < 1 (u k,n ) nN d 2

1

k a

n

=

1, · ·

·

, k

n

>

k

d 2 ((u k,n ) nN , 0) = k 0.5a

d 1

d 1 d 2 l 1

X T

T

X

X T

T

T

f : X Y

f (x) U x f (U ) V

f X X

f

x f 1 (V ) V

x

f 1 (V )

f Y

X x X V Y f (x) W

f (x) W V U = f 1 (W ) x f (U ) V

f x

x X V

: X Y

V

Y

f (x) U

x U f 1 (V ) f 1 (V )

f (U ) V

R 2

k > 0 u 2k

= 1/k u 2k+1 = k

X X = [0, 1] [2, 3] R A = [0, 1]

f : Z Z

Z

Z

X = R A =] − ∞, 0[ X = R 2 A